PENGEMBANGAN DESAIN KARAKTER KOMIK WARAK NGENDOG BERBASIS NILAI-NILAI KEARIFAN LOKAL - khamadi; Senoprabowo, Abi (Jurnal Bahasa Rupa, 2021)
Warak Ngendog as a symbol of unity and the mascot of Semarang City. It has local wisdom values ​​which are important to be passed on to the younger generations. So far, Warak Ngendog has been close to people's lives in the form of toys and a Dugderan celebration which is held once a year. The trend shows that the Warak Ngendog toy is getting less and less popular, due to the presence of foreign characters that are closer to the child. This has made the younger generation's understanding of Warak Ngendog culture decrease. The purpose of this research is to design the comic characters of Warak Ngendog to attract public interest. This study uses a qualitative descriptive method to get a picture of the value of local wisdom of Warak Ngendog. This is then analyzed and implemented in designing a good comic character design. The results of the analysis show that aesthetic, social, and religious values ​​are the main elements in designing the character of Warak Ngendog. The result is a character design of Warak Ngendog which still maintains its visual uniqueness and has a good characterization of representation of Warak Ngendog's social and religious values.